2022
DOI: 10.1177/03000605221126039
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic angiocentric fibrosis of the sinonasal tract: a case report and review of the literature

Abstract: Eosinophilic angiocentric fibrosis (EAF) is a rare chronic benign disorder of unknown etiology and is characterized by submucosal thickening and fibrosis in the upper respiratory tract. In this report, we describe a case of EAF in the nasal cavity of a woman who underwent elective surgery for division of adhesions and has had no recurrence during 2 years of postoperative follow-up. A review of the literature on the clinical manifestations of EAF, sites of lesions, management, and outcomes identified 48 article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The characteristic histologic feature of EAF are as follows: a dense fibrotic stroma with a perivascular “onion skin-like” whorling pattern and a dense inflammatory infiltrate that the major cells are eosinophils, consisting of lymphocytes, plasma cells, and some neutrophils. [11] Microscopic pathology in our case showed proliferative fibrous tissue, eosinophils, lymphocytes and plasma cells. And they distributed in concentric circles around the vessel.…”
Section: Discussionmentioning
confidence: 57%
“…The characteristic histologic feature of EAF are as follows: a dense fibrotic stroma with a perivascular “onion skin-like” whorling pattern and a dense inflammatory infiltrate that the major cells are eosinophils, consisting of lymphocytes, plasma cells, and some neutrophils. [11] Microscopic pathology in our case showed proliferative fibrous tissue, eosinophils, lymphocytes and plasma cells. And they distributed in concentric circles around the vessel.…”
Section: Discussionmentioning
confidence: 57%
“…Nasal congestion, nasal bleeding, loss of smell and other symptoms can also be associated with naso-orbital communication lesions. Studies have shown that nasal congestion is the most common symptom of nasal EAF, appearing in about 66.7% of cases [ 1 ]. Six cases had extraocular-muscle involvement, mostly of the internal rectus muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological examination is the main standard for diagnosing EAF. The typical pathological manifestations are massive infiltration of eosinophils, plasma cells, lymphocytes, and fibroblasts around small blood vessels; thickening of matrix; and characteristic rotation of onionskin-like collagen fibers and mesh proteins around occlusive blood vessels, accompanied by positive expression of IgG4 and IgG [ 1 , 2 ]. EAF should be distinguished from orbital inflammatory pseudotumor, hemangioma, and granulomatous disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation